8.2k views
5 votes
What is the product of (negative 6) (negative 7) (negative 1)?

User JJaun
by
5.2k points

2 Answers

7 votes

Answer:

-42

Step-by-step explanation:

negative * negative = positive

positive * negative = negative

negative * positive = negative

(-6)(-7)(-1) =

= 42(-1)

= -42

User Heena Bawa
by
5.0k points
3 votes

Answer:

-42

Explanation:

negative * negative = positive

positive * negative = negative

negative * positive = negative

(-6)(-7)(-1) =

= 42(-1)

= -42

User Tom DeMille
by
5.5k points